An Outside Option Experiment - Binmore, Ken; Shaked, Avner; Sutton, John (Quarterly Journal of Economics, 1989)
In the economic modeling of bargaining, outside options have often been naively treated by taking them as the disagreement payoffs in an application of the Nash bargaining solution. The paper contrasts this method of predicting outcomes with that obtained from an analysis of optimal strategic behavior in a natural game-theoretic model of the bargaining process. The strategic analysis predicts that the outside options will be irrelevant to the final deal unless a bargainer would then go elsewhere. An experiment is reported which indicates that this prediction performs well in comparison with the conventional predictor.